Landslide and flood hazard index for mountain roads an example from the Stura di Demonte Valley, Italy - Barisone, G.; Onori, A. (Journal of Nepal Geological Society, 2000)
Road alignments in mountainous areas are subject to heavy damage due to rockslides and floods. The rehabilitation and maintenance works that would be necessary to solve these problems are very costly. In this paper, the authors present methodology for obtaining, in relatively short time, a sufficiently detailed thematic map in which road alignment is subdivided into segments corresponding to different hazard degrees. As an example for such methodology, a 30 km long stretch of the road alignment in the Stura di Demonte Valley (Piedmont, Northwestern Italy) was chosen. The geomechanical characteristics of rock and soil in the area were obtained at the beginning. Major landslide phenomena (mostly rockfalls and debris flows) damaging the road alignment were located. A qualitative hazard index (Hi) was then calculated by taking into account such factors as affected road length, type and dimensions of the landslide, soil properties, and vegetation. Major hazards from rivers result from potential floods, which may overflow or erode road structures and destroy bridges and minor crossings. Firstly, the maximum discharge of rivers in the study area was calculated using various hydrological methods. Secondly, river expansion limits were evaluated. Historical data on past flood levels were considered during this process. During the high floods, malfunctioning of brides and other crossing structures can often have very serious consequences. The efficiency level of such structures, therefore was judged, taking their down-flowing section into consideration. For each structure, a comparison between estimated maximum river discharge and allowable discharge level (function of bridge and riverbed characteristics) determines the adequacy index (Ai). Results of analysis of both flood and landslide hazard were then synthesised in the final hazard map, which shows with simple graphic symbols and an intuitive colour range (in order to allow easy consultation by non-experts), the most important hazard factors, pertinent protection works, and resulting hazard degrees for roads, bridges, and other structures.